Korelasi antara jumlah mikronukleus dan ekspresi 8-oxo-dG akibat paparan radiografi panoramic (The correlation of micronucleus formation and 8-oxo-dG expression due to the panoramic radiography exposure) - Rurie Ratna Shantiningsih; Suwaldi Suwaldi; Indwiani Astuti; Munakhir Mudjosemedi (Universitas Airlangga, 2013)
Background: The expression of 8-oxo-dG is defined as one form of damaged DNA occuring as the result of oxidation reaction due to X ray exposure. Panoramic radiography exposure has been widely known to be able to increase micronucleus which are signing the early stage and as biomarker in carsinogenesis mechanism. Purpose: The purpose of this research was to determine the correlation between micronucleus number and 8-oxo-dG expression as a result of panoramic radiography exposure. Methods: Twelve New Zealand male rabbits aging 6 months were divided into 4 groups. Group I were rabbits that represented 0 day, group II represented 3th day, group III represented 6th day, and group IV represented 9th day after the panoramic radiography exposure. Respectively samples were swabbed at mandibular anterior gingival mucosa before and after the panoramic radiography exposure. The swabbed samples were coloured by using Feulgen-Rossenbeck modified staining for calculating the amount of micronucleus formation. Expression of 8-oxodG was detected using immunohistochemical of rabbit's gingival mucosa epithelium. Statistical analysis were carried out on pearson correlation. Results: There was a highest increasing of micronucleus on the 9th day after panoramic radiography exposure. Meanwhile, there was significant correlation (p=0,049) of the increasing amount of micronucleus and 8-oxo-dG expression in negatively correlation (r = -0,578). The increasing of micronucleus formation on the 9th day after panoramic radiography exposure was accordance with some previous studies. The expression score of 8-oxo-dG decreases as the day goes by. Conclusion: There was a correlation between the number of micronucleus and expression score of 8-oxo-dG. <span style="font-family: Tribune-Bold; font-size: 10pt; color: #231f20; font-style: normal; font-variant: